Non Genetec Parameters and Repeatability for Milk Traits Goat in Northern Iraq - Baper, Mevan I.; Hermiz, Hani N. (Science Journal of University of Zakho, 2019)
A total of 439, 436 and 437 records of average daily milk yield (ADMY), milk yield after weaning (MYAW) and total milk yield (TMY) respectively were analyzed. Data used in this study obtained from mountain does at private project in Raselain Village/ Akre Region/ Duhok governorate. The data related to two milking seasons (2016-2017) and (2017-2018). The animals were allowed to graze natural pasture and stubble, straw and ground oak acorns were providing whenever required. Does were flushed 2 weeks prior to mating and kidding season. The flock was placed on a regular health program. Does were milked by hand at biweekly intervals starting from the first week post kidding till the does are dried off. ADMY was calculated by multiplying test day milk yield * 2. While TMY calculated by multiplying ADMY by lactation period. Statistical analysis of data was carried out by using GLM procedure within SAS programme. This model includes effects of doe's age, year and season of kidding, birth's type and sex and weight of doe at kidding on milk traits. Effect of doe added to above model as a random effect to estimate their repeatability using Restricted Maximum Likelihood method. Overall means for ADMY, MYAW and TMY were 0.727, 54.49 and 129.32 kg respectively. Results showed that the age of does had significantly higher effect (P< 0.01) on all studied traits of milk. Does aged 4.5 years produce significantly higher ADMY (0.772 kg), and accordingly TMY (136.88kg), while higher MYAW recorded for does aged 3.5 years beside 4.5 years. The effectiveness of year was significant (P< 0.01) on all milk yield traits. Also season of kidding affect all studied milk traits significantly (P< 0.01), whereas the does kidding in winter had significantly higher ADMY, MYAW and TMY than those kidding in spring season. The effects of type of birth and sex of kids were significant on all milk traits. Does with female twins produced significantly more ADMY comparing with does having male or female singles only. Does with female twins and male and female twins produced significantly much MYAW. Does with female twins yield significantly higher TMY when compared to those in the other groups, on the same time there were no significant differences in TMY of does with male twin and does with male and female twin. There was no significant effect of doe weight at kidding on all studied traits and the regression coefficients were positive for ADMY (0.0003 kg/kg), and TMY (0.085 kg/kg) while the regression was negative for MYAW (- 0.0024 kg/kg). Repeatability estimates of ADMY, MYAW and TMY were 0.24, 0.31 and 0.27 respectively.It sum: due to the effectiveness of the fixed factors on the studied traits, hence adjusting records is necessary. The estimates of repeatability indicate that selection of does as well their kids depending on their milk production will improve the productivity in the next year.
Keywords: Mountain Goat; Milk Traits; Genetic Non-Genetic Effects; Repeatability